The Effect of Trust Dimensions Towards Online Purchase Intention Of Consumers And Potential Consumers (Online Vegetables Shopping) (Journal of Business and Management, 2022)
Abstract. E-commerce users in Indonesia continue to increase especially during the Covid-19 outbreak. This condition makes many business from various sectors try to sell their product online, one of which is vegetables product. However, people’s intention to buy vegetables online has not developed rapidly. People prefer to buy vegetables directly to the markets because there is still a lack of trust in online vegetable service providers. Based on this phenomenon, research about the effect of trust dimensions towards online purchase intention of consumers and potential consumers is conducted. This research was conducted by spreading a questionnaire with consumers and potential consumers. By using final data from 50 consumers and 73 potential consumers, analysis data is conducted using Microsoft Excel and SPSS, which are examined by multiple linear regression. The result of this study indicates that the trust dimension simultaneously has significant influence on consumers’ and potential consumers’ online purchase intention. For consumers, Ability has significant influence towards online purchase intention. Meanwhile, Integrity and Benevolence have no significant influence. For potential consumers, Benevolence has the strongest influence followed by Ability. Whereas, Integrity has no significant influence on potential consumer online purchase intention. The dimension of trust has a greater influence on potential consumers’ online purchase intention than consumers’ online purchase intention.Keywords: Trust Dimension, Integrity, Benevolence, Ability, Online Purchase Intention, Vegetables